FePt nanodendrites with high-index facets as active electrocatalysts for oxygen reduction reaction. (January 2015) - Wang, Di-Yan; Chou, Hung-Lung; Cheng, Ching-Che; Wu, Yu-Han; Tsai, Chin-Ming; Lin, Heng-Yi; Wang, Yuh-Lin; Hwang, Bing-Joe; Chen, Chia-Chun
Abstract: In this study, three different types of alloyed FePt nanostructures, nanodendrites, nanospheres and nanocubes, were prepared and their catalytic activities for oxygen reduction reaction (ORR) were studied. The ORR catalytic activity of the nanostructures was increased in the order of E-TEK Pt/C<FePt nanospheres<FePt nanocubes<FePt nanodendrites. In particular, a cation exchanging reaction was developed for the preparation of FePt nanodendrites, consisting of a dense array of branches on a core. The FePt nanostructures were analyzed by high-resolution transmission electron microscopy (HRTEM), high angle annular dark field (HAADF), scanning transmission electron microscopy (STEM) and electron energy loss spectrum (EELS) mapping. The HRTEM images revealed that the large surface area of FePt nanodendrites with a high density of atomic steps was enclosed by high-index 311 facet. The density functional theory simulation was performed to understand the origins of the enhanced electrochemical activity of FePt nanodendrites. The enhancement could be attributed to the exposure of high-index 311 facet of the nanodendrite with high surface energy in comparison to that low-index 111 and 200 facets of FePt nanospheres and nanocubes, respectively. Our experimental and theoretical studies have opened a route toward the syntheses of new nonprecious alloyed nanostructures to replace Pt as active fuel cell catalysts. Highlights: FePt nanodendrites enclosed by high-index 311 facet were prepared. DFT calculation indicated 311 facet of FePt nanodendrites has high surface energy. The trend of ORR activity: FePt nanodendrites>FePt nanocube>FePt nanoparticle.